Optimization of On-Grid Solar Power Plant Design for Urban Residential Areas: Case Study in Indonesia - Suseno, Doni; Hikariantara, I Putu; Tahir, Usman; Irwanto, Miko Mei (Journal of Renewable Engineering, 2025)
The increasing demand for electricity in urban areas of Indonesia demands diversification of sustainable energy sources. On-grid Solar Power Plants (PLTS) are a strategic alternative to reduce dependence on fossil fuels and increase household energy resilience. However, optimizing PLTS design still faces technical and structural challenges, such as the mismatch between panel production capacity and electricity consumption patterns, limited space, and weak regulatory support and fiscal incentives. This study uses a qualitative approach with a case study in an urban housing complex to examine the design process, implementation, and obstacles of on-grid PLTS. Data were obtained through in-depth interviews, field observations, and studies of policy and technical documents. The results of the study indicate that the success of PLTS implementation is highly dependent on a design that is contextual to the technical and social characteristics of housing, the support of fiscal policies such as initial subsidies, and institutional integration between communities, local governments, and the private sector. In addition, community-based approaches such as energy cooperatives can increase inclusive system adoption. This study concludes that on-grid PLTS is not only a technical solution for the clean energy transition, but also an instrument of socio-economic transformation that requires multidimensional synergy in its implementation in the urban environment of Indonesia